2009
DOI: 10.1111/j.1440-1843.2008.01476.x
|View full text |Cite
|
Sign up to set email alerts
|

Varenicline for smoking cessation: A placebo‐controlled, randomized study

Abstract: Varenicline was significantly more efficacious for smoking cessation than placebo over a 12-week treatment period and a further 12-week non-treatment follow-up period in smokers from China, Singapore and Thailand. No significant side-effects were noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
4
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 20 publications
5
62
4
6
Order By: Relevance
“…We found seven published RCTs conducted in generally healthy smokers, with at least one arm using varenicline 1.0 mg twice a day for 12 weeks, serving as our external comparison studies. [28][29][30][31][32][33][34] Incidence rates in overall AE and nausea in our study were comparable to those in external comparison studies (Table 3), however, we had a significantly higher incidence rate of abnormal dreams (31% versus 9%, p < 0.001) and a higher discontinuation rate (28% versus 13%, p = 0.011).…”
Section: Safety and Tolerabilitysupporting
confidence: 84%
See 1 more Smart Citation
“…We found seven published RCTs conducted in generally healthy smokers, with at least one arm using varenicline 1.0 mg twice a day for 12 weeks, serving as our external comparison studies. [28][29][30][31][32][33][34] Incidence rates in overall AE and nausea in our study were comparable to those in external comparison studies (Table 3), however, we had a significantly higher incidence rate of abnormal dreams (31% versus 9%, p < 0.001) and a higher discontinuation rate (28% versus 13%, p = 0.011).…”
Section: Safety and Tolerabilitysupporting
confidence: 84%
“…We also detected small but statistically significant changes in diastolic blood pressure, which were not associated with weight change. On the other hand, in three external comparison studies we used, only one case of ALT elevation was reported respectively, 28,30,31 and no significant change in blood pressure was reported in any external comparison study. Although inconclusive, due to limitations in our study, our results suggest that HIV-positive patients taking varenicline may benefit from monitoring of their liver enzymes and blood pressure.…”
mentioning
confidence: 92%
“…After the removal of duplicates and screening of titles and abstracts, 68 trials underwent full‐text review. In total, 38 RCTs met all eligibility criteria and were included in our meta‐analysis 10, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies matching the inclusion criteria that evaluated cytisine were identified, 17,43 compared with 21 studies of varenicline. 16,[37][38][39]41,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] The varenicline data include studies of its clinical effectiveness in a number of real-world settings, which allows their results to be generalised to wider populations. Cytisine has yet to be studied in subpopulations.…”
Section: Strengths and Limitations Of The Reviewmentioning
confidence: 99%